Dansk standard for indholds- og strukturbeskrivelse af leksikalske datasamlinger - Eksempler på anvendelser i leksikografisk arbejde - Braasch, Anna (Nordiske Studier i Leksikografi, 1997)
Tue fust version of aProposal for Danish Standard: Lexical data collections - Description of data categories and data structure - Part 1: Taxonomy for the classification of information types has been sent out for comments by Dansk Standard (The Danish Standard Association). This contribution deals with two main applications ofthe taxonomy: description ofthe information content of an existing lexical data collection for exchange/reuse purposes and planning of a new lexical data collection with a view to reusability. Tue Centre for Language Technology had the opportunity to work experimentally with both applications ofthe taxonomy within the framework of different projects. We provide here a brief description of the tasks where we applied the taxonomy. We conclude with some relevant aspects of our experience with the application ofthe taxonomy.